2020
DOI: 10.4081/or.2020.8844
|View full text |Cite
|
Sign up to set email alerts
|

Total talar prosthesis with and without ankle ligament reconstruction using the three-dimensional computer-aided design and computer numerical control manufacturing techniques

Abstract: Severe damage and bone loss of the talus are problematic issues because of its unique shape, function, and characteristics. This present study’s objective is to propose the process of customized total talar prosthesis manufacturing, using three-dimensional (3D) Computer-Aided Design (CAD) with Computer Numerical Control (CNC) production along with evaluation of the results of total talar prosthesis replacement with or without ankle ligament reconstruction in patients with severe conditions of talus. The case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Kadakia et al 9 reported 1 patient with distal tibial AVN and Abramson et al 1 reported 1 of 8 patients with minor tibial wear. Angthong and Rajbhandari 2 did not find any radiologic signs of loosening. Morita et al reported tibiotalar osteophyte changes in 47% preoperatively and in 90% postoperatively.…”
Section: Ttrmentioning
confidence: 84%
See 1 more Smart Citation
“…Kadakia et al 9 reported 1 patient with distal tibial AVN and Abramson et al 1 reported 1 of 8 patients with minor tibial wear. Angthong and Rajbhandari 2 did not find any radiologic signs of loosening. Morita et al reported tibiotalar osteophyte changes in 47% preoperatively and in 90% postoperatively.…”
Section: Ttrmentioning
confidence: 84%
“…Three studies analyzed gait. One patient of 5 in the study by Angthong and Rajbhandari 2 had stiffness in the subtalar joint and 1 had limited weightbearing due to pain. Abramson et al 1 found 7 of 8 patients had decreased subtalar ROM and minor gait abnormalities, with 3 also suffering fixed hindfoot varus and 3 discomfort on ankle movement.…”
Section: Ttrmentioning
confidence: 98%
“…With the development of digital orthopedics and additive manufacturing technologies, three-dimensional printed (3D printed) talus body prosthesis or total talus prosthesis has been gradually applied in talus reconstruction [ 17 19 ]. In patients managed with 3D printed talus prosthesis following talus necrosis, it was reported a certain extent of joint mobility recovery; significant improvement of the limb function with early weight-bearing activities allowed and negligible leg length dis crepancy [ 20 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the rarity of talus malignant tumors, there are very few reports on the reconstruction of the talus [ 7 ]. Additionally, most literatures are confined to the case reports, resulting in the unclear clinical efficacy of 3D printed talus prosthesis approach in management of talus malignant tumor patients [ 17 19 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, this involves a modified Brostrom procedure to address chronic lateral ankle instability at the time of the TAR procedure. As a corollary, it should also be critical to achieve ligamentous stability for TTR and TATTR constructs to optimize outcomes [12][13][14][15][16] .…”
mentioning
confidence: 99%